The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1104/pp.107.112748
|View full text |Cite
|
Sign up to set email alerts
|

Pyrroloquinoline Quinone Is a Plant Growth Promotion Factor Produced by Pseudomonas fluorescens B16

Abstract: Pseudomonas fluorescens B16 is a plant growth-promoting rhizobacterium. To determine the factors involved in plant growth promotion by this organism, we mutagenized wild-type strain B16 using VKm elements and isolated one mutant, K818, which is defective in plant growth promotion, in a rockwool culture system. A cosmid clone, pOK40, which complements the mutant K818, was isolated from a genomic library of the parent strain. Tn3-gusA mutagenesis of pOK40 revealed that the genes responsible for plant growth prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
137
0
4

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(148 citation statements)
references
References 62 publications
(53 reference statements)
4
137
0
4
Order By: Relevance
“…This compound has been attributed with multiple physiological functions such as regulation of electron transport system (Kobayashi et al, 2005), enhancing the adaptability of microbes ( Khairnar et al, 2007), improving the growth of plants ( Choi et al, 2008) and stimulating the production of nerve growth factor (Yamaguchi et al, 1993), thus presenting a wide application prospect in pharmaceutical, agriculture and food industries (Andrea et al, 1999;Rucker et al, 2009;Misra et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…This compound has been attributed with multiple physiological functions such as regulation of electron transport system (Kobayashi et al, 2005), enhancing the adaptability of microbes ( Khairnar et al, 2007), improving the growth of plants ( Choi et al, 2008) and stimulating the production of nerve growth factor (Yamaguchi et al, 1993), thus presenting a wide application prospect in pharmaceutical, agriculture and food industries (Andrea et al, 1999;Rucker et al, 2009;Misra et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies with bacterial mutants unable to produce PQQ and gluconic acid have demonstrated the intimate relation of the cofactor to phosphate solubilization processes (7,17). Besides its relevant role in P solubilization, PQQ is reported to be a potent growth-promoting factor for bacteria and plants, has antioxidant properties (5), and is directly related to the production of antimicrobial substances (7,14,36) as well as to the induction of systemic plant defenses (17). Hence, the cofactor PQQ has multiple plant beneficial effects.…”
mentioning
confidence: 99%
“…The genes responsible for PQQ production have been cloned and sequenced in several bacterial genera, including Pseudomonas, Methylobacterium, Acinetobacter, Klebsiella, Enterobacter, and Rahnella (5,14,17,36,42). In P. fluorescens B16, the PQQ operon is formed by 11 …”
mentioning
confidence: 99%
“…Additionally, it has been reported that PQQ plays a role beyond that of a cofactor of the PQQ-dependent dehydrogenase. PQQ promotes growth of both mammals and plants because of its antioxidant activity (14,48) and is also found to be a chemotactic attractant for Escherichia coli (15).…”
mentioning
confidence: 99%